EKTOPARASIT (PROTOZOA DAN HELMINTHES) PADA LALAT DI PASAR JOHAR DAN PASAR PETERONGAN KOTA SEMARANG ECTOPARASIT (PROTOZOAN DAN HELMINTHES) ON THE FLIES AT JOHAR AND PETERONGAN MARKETS SEMARANG CITY - Meilinda Hilda Ryani; Retno Hestiningsih; Mochamad Hadi (Jurnal Kesehatan Masyarakat (Undip), 2017)
Flies can play a role as mechanic vector in the transmission of disease. This is due to the behavior of flies that like dirty and moist places. Traditional markets have potential in the presence of flies because there are many food source for flies such as garbage, vegetable residue, and fresh or rotten meat. The purpose of this study was to determine the diversity of ectoparasites (protozoa and helminthes) on the fly at Johar and Peterongan Markets in Semarang. This was an explorative study which was conducted by survey method and laboratory examination with cross sectional approach. The population of the study were all flies contained in Johar and Peterongan. Sampling was done by accidental sampling at three spots (garbage dump, meat selling area and fish selling area). Flies caught in both markets were 338 heads consisting of 74% Chrysomya megacephala and 26% Musca domestica. The results showed that 6.25% of the flies caught in the Johar market positively carried the worm Trichuris sp. egg and hookworm egg, whereas 31,25% of flies in Peterongan market possitively carried the cyst of Blastocystis sp., Chilomestix sp., and Isospora sp. as well as the egg of worm Capillaria sp.